Ocular manifestations of cavernous sinus thrombosis - Visvanathan, V (BMJ Publishing Group, 2010)
A 17-year-old male presented with a 10-day history of symptoms of upper respiratory tract infection, headaches, photophobia and progressive swelling around both eyes. Clinical examination revealed a temperature of 39 °C and bilateral periorbital swelling which was worse on the left side. Initial ophthalmological examination revealed a dilated non-reactive pupil on the left side and a sluggish pupillary reflex on the right side. The patient also had a lateral rectus palsy of the left eye. Fundoscopy showed bilateral papilloedema, and visual acuity on admission was 6/12 in the right and 6/18 in the left eye. Ear, nose and throat examination revealed a rhinitic nasal mucosa with thick mucopus in the left middle meatus. The patient required surgical intervention to drain his sinuses followed by long-term intravenous antibiotic therapy and anticoagulation. After 6 weeks of therapy and close observation, he recovered with minimal sequelae.